Investigation of students' comfort and adaptation in university dormitories in humid subtropical climatic area in winter in Chongqing, China. Issue 1 (1st January 2021) - Mmereki, Daniel; Akpaca, Wilfried Denis
Abstract: Students' comfort and adaption in university dormitories is important for their learning. By controlling different environmental parameters (temperature, humidity, air velocity, etc., ) this can provide a great satisfaction in students' dormitory. In the present study, investigation was performed in students' dormitories in university in Chongqing, China. A survey was conducted on students' thermal comfort in typical university dormitories during winter in Chongqing, Southwest China. This also included on-site and continuous measurements of indoor physical parameters and filling out questionnaires about thermal sensation, thermal comfort, and adaptive behaviours by the students. Results showed that staying for longer periods in regions with a colder climate in winter, improved students' adaptability to lower temperature, closely correlated to behavioural and psychological processes. Although the thermal conditions varied in the international students' and Chinese students' dormitories, the thermal environmental conditions in the students' dormitories were poorer. The average indoor air temperature was 18.7°C and 18.1°C in the international students' and Chinese students' dormitories, respectively, which fell outside the ASHRAE thermal comfort zone, with higher indoor relative humidity. In addition, Chinese students felt more comfortable and satisfied with indoor air temperature and relative humidity compared to international students, evidently showing a higher adaptability to a severe colder winter climate. The study provides information that can support comfort researchers, designers, and policy makers towards improved design in student's dormitories and sustainable dormitory buildings.